Currency Conversion of Fama/French Factors: How and Why? - Glück, Maximilian; Hübel, Benjamin; Scholz, Hendrik (Journal of Portfolio Management, 2020)
Investors and researchers around the world use Fama/French factors in empirical studies. Most convenient is to download those factors in U.S. Dollars from databases like Kenneth French’s data library. When working from a non-U.S. perspective without converting the currencies of the factors, estimations of both alphas and factor loadings could be affected by exchange rate fluctuations. In this paper we show how to convert Fama/French factors into currencies other than U.S. Dollars. We also illustrate the statistical and economical relevance of the currency conversion based on performance and style analysis of more than 1,700 European equity funds and common European market indices

ESG Rating Events and Stock Market Reactions - Glück, Maximilian; Huebel, Benjamin; Scholz, Hendrik (2022)